2009
DOI: 10.1073/pnas.0901781106
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genome-scale analysis of protein localization in an asymmetric bacterium

Abstract: Despite the importance of subcellular localization for cellular activities, the lack of high-throughput, high-resolution imaging and quantitation methodologies has limited genomic localization analysis to a small number of archival studies focused on Cterminal fluorescent protein fusions. Here, we develop a highthroughput pipeline for generating, imaging, and quantitating fluorescent protein fusions that we use for the quantitative genomic assessment of the distributions of both N-and C-terminal fluorescent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
160
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 23 publications
4
160
0
2
Order By: Relevance
“…Some have hypothesized that intrinsically disordered hub proteins are advantageous in complex systems because they simplify multicomponent networks by allowing many binding partners to be organized around a single hub (15,14). Dozens of different proteins are localized specifically to Caulobacter cell poles (2). In this light, the role of PopZ in organizing such a complex network in bacteria is consistent with the functions of other intrinsically disordered hub proteins.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some have hypothesized that intrinsically disordered hub proteins are advantageous in complex systems because they simplify multicomponent networks by allowing many binding partners to be organized around a single hub (15,14). Dozens of different proteins are localized specifically to Caulobacter cell poles (2). In this light, the role of PopZ in organizing such a complex network in bacteria is consistent with the functions of other intrinsically disordered hub proteins.…”
Section: Discussionsupporting
confidence: 54%
“…In rod-shaped bacteria, the cell poles are also sites for the assembly of complex structures. Electron microscopy has shown that the cytoplasm at the cell poles in Caulobacter is visibly distinct from other areas of the cytoplasm (1), and a genome-wide screen identified more than 80 different proteins that are localized to these locations (2). Although some of these proteins are known to require the presence of an upstream recruitment factor, a fully ordered system of polar assembly has not been established.…”
mentioning
confidence: 99%
“…1) because they were most abundant within the log-phase population under study (Experimental Procedures). For quantitative image analysis, we used Projected System of Internal Coordinates from Interpolated Contours (PSICIC), a program originally developed for elongated cells such as E. coli and Caulobacter crescentus (31,32). We extended the program to record the fluorescence intensity at the perimeter of ovococcal and diplococcal E. faecalis cells, enabling the rapid quantification of localized fluorescence measurements at the membrane of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, no molecular probes for the study of the stalk ultrastructure and biogenesis were known. Conducting a cytological survey of 75% of the predicted translation products of Caulobacter, Werner et al uncovered candidate proteins that appear associated with the stalk (6). The stalk is a cylindrical protrusion of all envelope layers (inner membrane, periplasm, outer membrane, and S-layer) at the old cell pole and encloses cytoplasmic material that is free of chromosomal DNA, ribosomes, and most cytoplasmic proteins (7,8).…”
mentioning
confidence: 99%